Experimental Verification of the Identity of Variant-Specific Surface Proteins in Giardia lamblia Trophozoites - Wei Li (American Society for Microbiology, 2013)
ABSTRACT The cell membrane of a Giardia lamblia trophozoite is covered with a single species of variant-specific surface protein (VSP) that is replaced by another VSP every 6 to 13 generations of cell growth, possibly for an evasion of host immunity. Experimentally, only six VSP species have been verified to localize to the cell membrane thus far. By assuming that VSP contains multiple CXXC motifs, 219 vsp genes were annotated in GiardiaDB of the WB isolate. By further assuming that VSP possesses both CXXC motifs and a CRGKA tail at the C terminus, Adam et al. (BMC Genomics 11:424, 2010) identified a total of 303 potential vsp genes in Giardia WB. The discrepancies between these two assumed VSP identities have caused some confusion. Here, we used experimental approaches to further verify what is required of the structures of a VSP to localize to the surface of cell membrane. The data led to the following conclusions. (i) The C-terminal CRGKA sequence is not essential for localizing VSPs to the cell membrane. (ii) A “motif 1” of 45 residues, consisting of two CXXCs separated by 12 to 15 amino acid residues, located close to the C terminus and a hydrophobic “motif 2” of 38 residues at the C terminus are both essential and sufficient for localizing the protein to the cell membrane. (ii) An N-terminal sequence upstream from motif 1 is not required for targeting VSPs to the cell membrane. By these criteria, we are able to identify 73 open reading frames as the putative vsp genes in Giardia. IMPORTANCE The intestinal pathogen Giardia lamblia expresses only one variant-specific surface protein (VSP) on the cell membrane surface at a given time, but it changes spontaneously every 6 to 13 generations of growth, presumably for evading the host immunity. Only 6 VSPs have been empirically shown to localize to the cell membrane surface thus far. Here, we used mutations of VSPs and methods of identifying their locations in Giardia cells and found that a “motif 1” of 45 residues, consisting of two CXXCs separated by 12 to 15 amino acid residues, located close to the C terminus and a hydrophobic “motif 2” of 38 residues at the C terminus are the only essential and sufficient structural requirements for localizing a protein to the cell membrane. By these criteria, 73 genes are identified in the Giardia WB strain genome database as the putative repertoire of VSPs.